الفكري اللغوي بين الجرجاني وتشومسكي من خلال نظريتي النظم والتوليدية - Hassan, Ahmed Osman Fedail (Journal of Arabic Education and Linguistics, 2025)
<div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="3c0ba9fb-dec4-40da-a515-903ea30dfd50" data-message-model-slug="gpt-4o"> This study aims to explore the points of convergence and similarity between the linguistic thought of the Arab scholar ʿAbd al-Qāhir al-Jurjānī and contemporary linguistic theories, particularly the contributions of scholars in the field of transformational-generative linguistics. This exploration aligns with the call to revisit and reinterpret Arab intellectual heritage in light of contemporary linguistic concepts, thereby creating a meaningful connection between the two to enrich modern linguistic studies across diverse contexts. The research focuses on ʿAbd al-Qāhir al-Jurjānī, the proponent of the "Nazm" theory, to compare his ideas with the transformational-generative theory due to the significant points of alignment between the two frameworks. For instance, Chomsky’s theory resembles al-Jurjānī’s thought in its conceptualization of "precedence and succession," as it emphasizes the primacy of certain linguistic elements over others within a syntactic structure. Moreover, Chomsky’s theory has become a dominant paradigm in linguistic studies, and no linguistic school has refrained from engaging with or positioning itself in relation to his ideas.